2014
DOI: 10.7314/apjcp.2014.15.16.6505
|View full text |Cite
|
Sign up to set email alerts
|

Association of a miR-502-Binding Site Single Nucleotide Polymorphism in the 3'-Untranslated Region of SET8 and the TP53 Codon 72 Polymorphism with Cervical Cancer in the Chinese Population

Abstract: Objective: This study was conducted to identify whether polymorphic variants of set domain-containing protein 8 (SET8) and tumor protein p53 (TP53) codon 72, either independently or jointly, might be associated with increased risk for cervical cancer. Methods: We genotyped SET8 and TP53 codon 72 polymorphisms of peripheral blood DNA from 114 cervical cancer patients and 200 controls using the polymerase chain reactionrestriction fragment length polymorphism (PCR-RFLP) and direct DNA sequencing. Results: The fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…The missense variant of TP53 c.215C > G, corresponding to codon P72R, is the most studied SNV among the cardiovascular, endocrine, gastrointestinal and genetic categories. In a Chinese study in 323 cervical cancer patients and 568 normal samples, it was found that the CG genotype is a risk factor for the development of cervical cancer (p = 0.02) [29], and another study found that the genotype GG is associated with cervical cancer [30]. Despite that, this TP53 variant was not found to be associated with 43 squamous cell carcinoma (SCC) and 67 cervical intraepithelial neoplasia (CIN) samples in another study [24].…”
Section: Variant Profiles Of Biomarkersmentioning
confidence: 99%
“…The missense variant of TP53 c.215C > G, corresponding to codon P72R, is the most studied SNV among the cardiovascular, endocrine, gastrointestinal and genetic categories. In a Chinese study in 323 cervical cancer patients and 568 normal samples, it was found that the CG genotype is a risk factor for the development of cervical cancer (p = 0.02) [29], and another study found that the genotype GG is associated with cervical cancer [30]. Despite that, this TP53 variant was not found to be associated with 43 squamous cell carcinoma (SCC) and 67 cervical intraepithelial neoplasia (CIN) samples in another study [24].…”
Section: Variant Profiles Of Biomarkersmentioning
confidence: 99%
“…This SNP was subsequently shown by others to be a susceptibility factor for a number of cancers, including non-small cell lung cancer [23], epithelial ovarian cancer [24], childhood acute lymphoblastic leukemia [25], and cervical cancer [26]. This broad spectrum of association suggests that this SNP is a robust genetic regulatory factor fundamental to cells.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, 13 studies involving 2866 patients and 3012 controls were included in our meta-analysis [ 23 , 31–42 ]. All of the subjects in these thirteen studies were from Asian countries, including nine case–control studies involving 2212 cases and 2314 controls conducted in Chinese populations [ 23 , 31–35 , 37 , 38 , 41 ], and four case–control studies involving 654 cases and 698 controls conducted in Iranian populations [ 36 , 39 , 40 , 42 ]. Population-based controls were used in seven studies [ 23 , 31–33 , 35–37 ] and hospital-based controls were used in six studies [ 34 , 38–42 ].…”
Section: Resultsmentioning
confidence: 99%